MORALITAS INDIVIDU, MANAJEMEN LABA, SALAH SAJI, PENGUNGKAPAN, BIAYA DAN MANFAAT, SERTA TANGGUNG JAWAB DALAM ETIKA PENYUSUNAN LAPORAN KEUANGAN - Bayusena, Ingrid Saraswati; Suartana, I Wayan; Badera, I Dewa Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.10.TAHUN 2016, 2016)
This research was conducted to appraise the perception of students Maksi and PPAk regarding ethics compilation of financial statement. This research used for the distinction of perception  of students Maksi and PPAk about individual morality, earnings management, misstate, disclosure, cost and benefit, and responsibility ethics compilation of financial statement. The data collection methods in this research is using with survey method by questionnaire technique. The number of samples in this research are 94 respondents were selected by on purposive sampling. The analysis technique used is the analysis of the Mann-Whitney U Test. The results showed that there was no difference between the perception of students Maksi and PPAk about individual morality, earnings management, misstate, disclosure, cost and benefit, while the responsibility to show the difference of perception in the ethics compilation of financial statement.
Keywords: Individual morality, earnings management, misstate, disclosure, cost and benefit, responsibility